Pengaruh Model Team Accelerated Instruction Terhadap Hasil Belajar Ditinjau Dari Keaktifan Siswa - Wide Sumiati; A.A Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2018)
This study aims to find out the effectiveness of TAI model through mathematics learning outcomes in terms of students' student activity. This research was a quasi-experimental research. Sampling technique in this research used Cluster Random Sampling technique. Data collection technique used questionnaire and tests. The data analysis technique used two-way variance analysis with unequal cell. The result of this research was that learning using TAI model is not more effective to use (Fobs< Ftable) with 2.859 <4.00; Students who have high student activity, have mathematics learning outcomes that are no better than those with moderate and low-skilled students (Fobs< Ftable) with 0.5576 < 3.15; There is no interaction between the learning model used and the student activity to the students' mathematics learning outcomes (Fobs< Ftable= 0.44 <3.15). A suggestion on the results of this study is in the process of teaching and learning teachers should be able to create an atmosphere of learning that can make students become more active.